SLC26 family: a new insight for kidney stone disease - Li, Jialin; Huang, Sigen; Liu, Shengyin; Liao, Xinzhi; Yan, Sheng; Liu, Quanliang (Frontiers in Physiology, 2023)
The solute-linked carrier 26 (SLC26) family is a class of multifunctional transporters with multiple folded conserved sequences in the structures involved in the transport of various substrates including oxalate, sulphate and chloride to maintain anion homeostasis in humans. In healthy individuals, alterations in anion homeostasis are one of the common factors contributing to stone development, such as hyperoxalemia/uria, leading to precipitation, adhesion of calcium oxalate and ultimately the formation of kidney stones. We found that the SLC26 protein is aberrantly expressed during kidney stone formation and is involved in the regulation of oxalate and several other anion metabolisms. In addition, inhibitors of individual SLC26 proteins exist, although they have not yet entered clinical trials, suggesting the possibility of this protein as a clinical stone treatment agent. In this review, we combine recent experimental reports as well as some clinical data to highlight the contribution of SLC26 protein in oxalate metabolism during stone formation, and discuss the potential limitations of current studies and possible directions for future development in this field.